PENGARUH KEPEMIMPINAN, MOTIVASI DAN IKLIM KERJA TERHADAP KOMITMEN PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN CIANJUR - Hermawan, Bubung Mukhtar (jurnal ekonomi, 2008)
This research is background to lower the of leadership, climate work and motivation employee its impact to commitment. This research use the quantitative method where data obtained in field to transformation into number so that can be by a statistical calculation, population and this sample research is all employee of sub districk of regency Cianjur which is all amounting to 78 and sample 65 people. Data analtysed by using regression analysis. Result of research lay open that: (1) there are influence which significant by together from leadership, climate work and motivation to commitment, (2) by parsial is leadership, climate work and motivation its impact to commitment. From this research result is suggested that by a head can improve the leadership, climate work and motivation employee on duty education regency Cianjur.